Program Wadai Bingka (Wadah Kami Belajar Meningkatkan Kesehatan): Dampak Pernikahan Dini, Kesehatan Reproduksi Dan Alat Kontrasepsi - Nani Kartinah; Pratika Viogenta; Sutomo Sutomo; Amalia Khairunnisa; Rezki Agustina (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
The negative impact of early marriage is the increased risk of maternal and child mortality, miscarriage, stunting in children, and poor reproductive health conditions. Wadai Bingka activities aim to increase public knowledge about the right marriage age, the importance of maintaining reproductive health and the use of contraceptives. The method used is in the form of education using an extension system, booklets, teaching aids and animated videos. There were 24 participants. Evaluation of activities is carried out by comparing the score values obtained by participants before the implementation of the activity (pre-test) and after the implementation of the activity (posttest). Based on the evaluation results, changes in participants' knowledge for good criteria increased by 84%, medium criteria decreased by 54%, and bad criteria decreased by 100%. It can be concluded that Wadai Bingka's service activities have a good impact as evidenced by an increase in community knowledge.